Improving students' writing skills of content and context aspect in biology using guided inquiry learning - Fitri, Annisa; Widoretno, Sri; Saputra, Alanindra (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
This research aimed to improve student writing skills in biology learning. The subjects of this research were 28 students in senior high school. This research was classroom action research carried out for 3 cycles. Each cycle consists of planning, implementation and observation, also reflection. Research instruments were assessment sheets containing the aspects of writing content and context-based on writing skills rubric assessment adapted from Mclean and Wyse (2012). The research procedure were carried out by taking action based on the results of the evaluation of each cycle which forms the basis for improvement in the next cycle. Writing skills data was validated using triangulation techniques: observation, interviews, and documentation. Data analysis used qualitative descriptive. The results showed that the scores for the quality of the content and the context of the students' writing in the pre-cycle were at scores of 2, 3, and 4 with an average of 42% for the quality of the content and 53% for the quality of the writing context, all at level 1. Improvement in scores and the average percentage occurs in cycles I, II, and III which occurs linearly according to the increase in the quality score of the problem formulation, the summary of the results of collecting and processing information, as well as the results of discussions and conclusions, thus the application of the Guided inquiry learning model improves students' writing skills in learning biology.